2015
DOI: 10.1007/s12541-015-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of friction stir processing on the thermal conductivity of a strain-hardened Al-Mg alloy

Abstract: Strain-hardened aluminum-magnesium alloy (aluminum 5052-H112 alloy) plates are successfully friction stir processed. The thermal conductivity of the FSPed aluminum alloy is consistently measured to be higher than that of the base metal, even though the amount of grain boundaries significantly increases in the FSPed zone due to grain size refinement by FSP as observed by electron back-scatter diffraction (EBSD) analysis. In terms of thermal conductivity of the selected strain-hardened aluminum alloy, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Following FSP with various combination, the tensile strengths slightly decrease while the elongations increases significantly. Hung et al [22] report the tensile strength of the received material AZ31-O sample as more than that of the FSP sample, while good ductility was attained with FSP.…”
Section: Tensile Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Following FSP with various combination, the tensile strengths slightly decrease while the elongations increases significantly. Hung et al [22] report the tensile strength of the received material AZ31-O sample as more than that of the FSP sample, while good ductility was attained with FSP.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…The grain structure after tensile failure remains equiaxed, but the grain size is quite different compared with the initial grain structure. Hung et al [22] concluded that AZ31-O specimen tensile strength was higher than FSP specimens, where the better ductility was achieved with FSP. Figure 7 shows the top surface and cross-section appearance of FSP in air, SFSP and CFSP AZ31B magnesium alloys.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…They do not explore the affinity of grain refinement's influence on conductivity [30,31]. Due to reduced dislocation density in the FSPed zone and minor grain development, the thermal conductivity of the FSPed aluminum 5052 alloy rises [32]. In addition, FSP increases the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%